MANAJEMEN ASET DAN HUTANG DALAM BANK SYARIAH - Andira, Agung Putra; Sitinjak, Marnala; Pendi, Irwansyah; Hendrawan, Yoni (Komunitas Manajemen Kompetitif, 2025)
This study uses desk research methodology to examine asset and liability management in Islamic banks. The main objective of this study is to understand the principles and mechanisms of asset and liability management, the differences between Islamic banks and conventional banks, the workings and efficiency of asset and liability management, and the risks and difficulties faced by Islamic banks. The research findings show that Islamic banks handle assets and liabilities in accordance with sharia principles such as the prohibition of usury and over- speculation, using sharia channels such as murabahah, mudarabah, and ijarah. The differences with conventional banks are mostly found in the operational and revenue streams. Islamic banking generally aims to achieve optimal efficiency in managing assets and liabilities, despite various risks and challenges such as adverse economic conditions and conflicts with conventional banks. Therefore, the management of assets and liabilities in Islamic banks has unique characteristics that necessitate the development of specialized lending strategies to achieve stability and efficiency. Keywords: Asset Management, Debt Management, Islamic Banks, Conventional Banks, Efficiency, Risks, Challenges, Sharia Principles.